Reduction in Mode-I SIF of an Edge Cracked C-Shaped Specimen Using Piezoelectric Actuator - Pattanayak Sourav; Pohit Goutam (E3S Web of Conferences, 2023)
The focus of the current research is on the feasibility of an adhesively bound piezoelectric actuator in the active repair of an edge-cracked C-shaped specimen. First, only constant uniaxial tensile loading is used to determine the Mode-I stress intensity factor. The Mode-I stress intensity factor is then examined while taking into account the actuation effect provided by the piezoelectric patch when an external voltage is applied. For an edge-cracked C-shaped specimen, the total stress intensity factor is determined analytically using the concept of the superposition principle of the linear-elastic crack problem. The outcome demonstrates a considerable decrease in the Mode-I stress intensity factor following active repair using the piezoelectric actuator. Parametric analysis has been carried out to comprehend repair performance and choose the best-sized actuators for active repair.